Comparative Evaluation of Penetration Ability of Three Pit and Fissure Sealants and Their Relationship with Fissure Patterns - Nikita Garg; KR Indushekar; Bhavna Gupta Saraf; Neha Sheoran; Divesh Sardana (Shiraz University of Medical Sciences, 2018)
Statement of the Problem: Pit and fissure sealant placement is considered as an effective modality for prevention of caries on occlusal surfaces. Penetration, retention and lateral wall adaptation are the key factors in success of pit and fissure sealant restorations. Purpose: The purpose of this paper was to compare penetration ability and lateral wall adaptation of three commercially available pit and fissure sealants. Materials and Method: The present in-vitro study was done on 45 extracted sound human molars to evaluate the fissure pattern and assess the penetration ability of three commercially available sealants [Delton® FS Sealant (Dentsply DeTrey GmbH, Konstanz, Germany), Clinpro™ Sealant (3M™ ESPE™, Minnesota, USA) and GC Fuji VII Glass Ionomer Cement (GC Asia Dental Pte Ltd, Singapore)] on molars divided into 3 equal groups of 15 each, with further sectioning of each sample into 2 parts giving 30 samples per group. Following thermocycling and embedding of teeth in clear auto-polymerizing acrylic resin, sections were evaluated for fissure morphology, sealant penetration, unfilled space, lateral wall adaptation, and for presence of voids. Results: Penetrability of all the sealants studied was found to be significantly more in U-type fissure pattern (93.89%) followed by V-type (78.62%), IK-type (74.34%) and then in I-type (65.91). The depth of penetration of the GC Fuji VII Glass Ionomer sealant (85.82%) was found to be superior followed by unfilled resin sealant (Clinpro™ Sealant- 78.26%) and then by filled resin sealant (Delton® FS Sealant- 74.89%). Conclusion: U- type fissure pattern was more common than other fissure patterns and showed significantly higher penetrability of different type of sealants evaluated in the present study. GIC based sealant, due to significantly higher penetration depth than unfilled and filled sealants used in the present study, can be preferred over filled or unfilled resin sealants.